GEÇİŞ METALİ ALAŞIMLARINDA AMORF YAPIDAN KRİSTAL YAPIYA DÖNÜŞÜMÜN MOLEKÜLER DİNAMİK YÖNTEMİ İLE İNCELENMESİ - ÇELİK, FATİH AHMET (Fırat Üniveristesi, 2010)
Bu çalışmada, Cu ve Ni mono-atomik sistemleri, CuNi, NiAl ikili alaşım sistemleri ve CuAlNi üçlü alaşım sistemi için atomlararası etkileşimler gömülmüş atom metodunun Sutton-Chen versiyonu kullanılarak modellendi. Model sistemler Parrinello-Rahman şekilce ve hacimce değişebilir moleküler dinamik (MD) yöntemi kullanılarak incelendi. Tüm sistemlerin faz dönüşümlerinin yapısal analizleri radyal dağılım fonksiyonu ile incelendi. Model sistemlerin sıvı fazdan yüksek soğutma hızı ile amorf faza dönüşümleri gerçekleştirildi ve amorf fazda farklı sıcaklıklarda bekletilerek kristal faza dönüşümler analiz edildi. Bu dönüşüm süreçlerinde, atomik topakların yapıları bağ yönelim düzeni parametreleri ve Honeycutt-Andersen (HA) metodu kullanılarak belirlendi. Üçlü alaşım sistemi için kristalleşme süresince, bağlı kristal çiftlerin yüzdesindeki değişim incelendi ve Johnson-Mehl-Avrami (JMA) denklemindeki Avrami üsteli değerleri iki farklı tavlama sıcaklığı için MD yöntemle hesaplandı. Sonuç olarak, amorf fazdan kristal faza dönüşüm sürecinde bağlı çiftlerin ve bağlı üçlülerin kristal fazın meydana gelmesinde önemli rol oynadığı belirlendi.

In this study, interatomic interactions have been modeled by using Sutton-Chen version of embedded atom method for Cu and Ni mono-atomic systems, CuNi, NiAl binary alloy systems and CuAlNi ternary alloy system. Model systems have been investigated by the molecular dynamics (MD) simulation technique of Parinello-Rahman which allows the MD cell to vary in shape and size. Structural analyses during the phase transformations of all the model systems have been investigated using radial distribution function. The transformations of the model systems from liquid phase to amorphous phase with a high cooling rate have been performed, and the transformations to crystal phase have been analyzed by holding the amorphous phase at different temperatures. During these transformations processes, structures of atomic clusters have been determined using the bond orientational order parameters and Honeycutt-Andersen (HA) method. Variations in the percentages of the bonded pairs in the crystals have been investigated during the crystallization period for ternary alloy, and Avrami exponential values in Johnson-Mehl-Avrami (JMA) equation have been calculated for two different annealing temperatures using MD method. As a result, during the transformation from amorphous phase to crystalline phase, it has been determined that the bonded pairs and the bonded triples have an important role in the formation of crystal phase.
Investigation of transformation from amorphous state to crystalline state for transition metal alloys by molecular dynamics method
Keywords: Fizik ve Fizik Mühendisliği